Posterior lamellar versus bilamellar tarsal rotation surgery for trachomatous trichiasis in Ethiopia: a randomised controlled trial. Issue 3 (March 2016) - Habtamu, Esmael; Wondie, Tariku; Aweke, Sintayehu; Tadesse, Zerihun; Zerihun, Mulat; Zewudie, Zebideru; Kello, Amir Bedri; Roberts, Chrissy H; Emerson, Paul M; Bailey, Robin L; Mabey, David C W; Rajak, Saul N; et al.
Summary: Background: Eyelid surgery is done to correct trachomatous trichiasis to prevent blindness. However, recurrent trichiasis is frequent. Two procedures are recommended by WHO and are in routine practice: bilamellar tarsal rotation (BLTR) and posterior lamellar tarsal rotation (PLTR). This study was done to identify which procedure gives the better results. Methods: A randomised, controlled, single masked clinical trial was done in Ethiopia. Participants had upper lid trachomatous trichiasis with one or more eyelashes touching the eye or evidence of epilation, in association with tarsal conjunctival scarring. Exclusion criteria were age less than 18 years, recurrent trichiasis after previous surgery, hypertension, and pregnancy. Participants were randomly assigned (1:1) to either BLTR or PLTR surgery, stratified by surgeon. The sequences were computer-generated by an independent statistician. Surgery was done in a community setting following WHO guidelines. Participants were examined at 6 months and 12 months by assessors masked to allocation. The primary outcome was the cumulative proportion of individuals who developed recurrent trichiasis by 12 months. Primary analyses were by modified intention to treat. The intervention effect was estimated by logistic regression, controlled for surgeon as a fixed effect in the model. The trial is registered with the Pan African Clinical Trials Registry (number PACTR201401000743135). Findings: 1000 participants with trichiasis were recruited, randomly assigned, and treated (501 in the BLTR group and 499 in the PLTR group) between Feb 13, 2014, and May 31, 2014. Eight participants were not seen at either 6 month or 12 month follow-up visits and were excluded from the analysis: three from the PLTR group and five from the BLTR group. The follow-up rate at 12 months was 98%. Cumulative recurrent trichiasis by 12 months was more frequent in the BLTR group than in the PLTR group (110/496 [22%] vs 63/496 [13%]; adjusted odds ratio [OR] 1·96 [95% CI 1·40–2·75]; p=0·0001), with a risk difference of 9·50% (95% CI 4·79–14·16). Interpretation: PLTR surgery was superior to BLTR surgery for management of trachomatous trichiasis, and could be the preferred procedure for the programmatic management of trachomatous trichiasis. Funding: The Wellcome Trust.